PENGARUH FLEKSIBILITAS KERJA,HYBRID WORKING,DAN SOFT SKILL TERHADAP KINERJAKARYAWAN (STUDI DILAKUKAN PADA DINAS KOPERASI DAN UMKM KABUPATEN LAMONGAN) - Sari, Dian Puspita; Syaikhudin, Ahmad Yani; Rozi, Ahmad Fathur (J-EEMB (Journal of Economic Entrepreneurship and Management Business), 2025)
This research aims to determine the effect of work flexibility, hybrid working, and soft skills on employee performance at the Lamongan Regency Cooperatives and UMKM Service. The approach used is quantitative with explanatory research methods. The sample in this research was all service employees, totaling 57 people. The data analysis technique uses multiple linear regression via SPSS version 26. The research results show that work flexibility, hybrid working, and soft skills have a positive effect on employee performance, both partially and simultaneously. Soft skills are the most dominant variable in improving performance. These findings show the importance of implementing flexible work systems and strengthening soft skills in increasing employee productivity, especially in government agencies.